Cobalt and nitrogen codoped ultrathin porous carbon nanosheets as bifunctional electrocatalysts for oxygen reduction and evolution. (January 2019) - Tang, Youchen; Liu, Ruliang; Liu, Shaohong; Zheng, Bingna; Lu, Yuheng; Fu, Ruowen; Wu, Dingcai; Zhang, Mingqiu; Rong, Minzhi
Abstract: Development of efficient, low-cost, and durable electrocatalysts for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is scientifically and technologically important for the conversion and storage of renewable energy. Herein, cobalt and nitrogen codoped ultrathin porous carbon nanosheet (Co-N-PCN) is developed by directly carbonizing the graphene oxide sandwiched cobalt ion adsorbed polyaniline- co -polypyrrole (PACP) precursors. The nitrogen-rich PACP favors the formation of abundant Co-Nx -C active species, while the 2D ultrathin nanosheet structure ensures the high exposure of the generated Co-Nx -C active sites to the electrolyte. In addition, the sandwiched graphene acts as the conductive backbone to facilitate fast charge transfer and enhance the electrode conductivity. Benefiting from the synergistic effect, the Co-N-PCN presents superior electrocatalytic properties with low overpotentials and favorable kinetics to Pt and RuO2 as a bifunctional electrocatalyst for ORR and OER. Remarkably, the potential difference of OER and ORR (Δ E  =  E j =10 - E 1/2 ) is as low as 0.81 V in 0.1 M KOH, indicating the Co-N-PCN outperforms most of the previously reported bifunctional electrocatalysts. Graphical abstract: Image 1